1981
DOI: 10.3406/ecoru.1981.4391
|View full text |Cite
|
Sign up to set email alerts
|

Une nouvelle approche de l'agriculture biologique

Abstract: [fre] L'agriculture biologique est une pratique agricole. Elle doit être abordée comme telle, c'est-à-dire en jugeant de la cohérence des actions entreprises par rapport aux objectifs poursuivis ; l'analyse de cette pratique est conduite au niveau de cinq exploitations agricoles qui s'en réclament. [eng] Biological farming is a set of husbandry pratices. They must be judged as such i. e. by estimating whether decisions taken are consistent with stated objectives. This analysis is conducted for five farms which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although this vision remained relatively dominant, other authors tried to rehabilitate organic agriculture and the farmers who practised it by analysing its technical foundations and subsequent balances, i.e., organic and mineral fertilisation, labour, assets, and liabilities (Bellon and Tranchant, 1981;Lockeretz, 1981), by looking at it as a social and economic practice and by acknowledging its technical and regional diversity (Cadiou et al, 1975). In this literature, organic farming is found to be a feasible alternative to conventional models (Viel, 1979;Gautronneau et al, 1981). In the USA, in this period of questioning over the limits of socalled modern agriculture, organic agriculture was considered a possible model (USDA, 1980), and other qualifications and definitions for agriculture also emerged, in particular "sustainable" (Harwood, 1990) and "alternative" agriculture (National Research Council, 1989).…”
Section: Introduction and Short Retrospectivementioning
confidence: 99%
“…Although this vision remained relatively dominant, other authors tried to rehabilitate organic agriculture and the farmers who practised it by analysing its technical foundations and subsequent balances, i.e., organic and mineral fertilisation, labour, assets, and liabilities (Bellon and Tranchant, 1981;Lockeretz, 1981), by looking at it as a social and economic practice and by acknowledging its technical and regional diversity (Cadiou et al, 1975). In this literature, organic farming is found to be a feasible alternative to conventional models (Viel, 1979;Gautronneau et al, 1981). In the USA, in this period of questioning over the limits of socalled modern agriculture, organic agriculture was considered a possible model (USDA, 1980), and other qualifications and definitions for agriculture also emerged, in particular "sustainable" (Harwood, 1990) and "alternative" agriculture (National Research Council, 1989).…”
Section: Introduction and Short Retrospectivementioning
confidence: 99%
“…These periods can be examined in three periods. The studies between 1970s and 1980s are the pioneering studies (Bellon and Tranchant, 1981;Gautronneau et al, 1981); the studies between 1990s and the early 2000s are on organic farming specialization (Padel et al, 1999;Padel, 2001;Demiryürek, 2000); and the recent studies are complex and detailed studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In examination of organic farming from sociological perspective addressed the organic farmers' attitude and practice (Le Pape and Remy, 1988). These studies were about evaluating organic farming as an alternative agricultural technique that can be applied (Gautronneau et al, 1981), encouraging transition to organic farming and the studies that show the social and geographical factors in transition to organic farming (Lamine and Bellon, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…But do these work requirements really put a brake on adoption? Other curbs are confirmed: regarding organic farming for example, Gautronneau 6 showed that a major obstacle to adoption in France was a fear of being marginalized, while a recent study 7 , carried out in California, proved the influence of management styles on adoption. Is the adoption of alternative agriculture systems hampered in Western countries, where everyone can make comparisons with the conditions in the productivity-driven farming system by the amount and nature of the work involved?…”
Section: Introductionmentioning
confidence: 98%